Barriers to Effective Prevocational education implementation in Jordanian Schools as Perceived by Teachers - Jawarneh, Tariq Yousef (Journal of Education and Vocational Research, 2013)
The main goal of this qualitative study was to explore perceptions and opinions of a group of in-service Prevocational Education (PVE) teachers to derive barriers to effective PVE implementation at the middle basic stage in Jordanian schools. The population and sample (n=35 of the study consisted of all teachers responsible for the delivery of PVE at the middle basic stage of the "North Mazar" educational directorate in the northern region in Jordan. The population and sample of the study were conveniently selected. The instrument used in this study was an interview schedule and technique used in analyzing data obtained from open-ended face-to-face interviews was that suggested by Merriam (2009) regarding qualitative data. Frequencies, percentages in addition to examples of sample quotes representing teachers’ responses were provided. The results revealed that PVE lack attractiveness for pupils, parents, teachers, and principals and consequently they hold negative attitudes towards this practical provision. The results revealed four categories of barriers: (1), Barriers pertaining to perceptions and attitudes (2) barriers pertaining to economic factors, (3) barriers pertaining to administrative factors, (4) Barriers pertaining to human factors. Discussions of such barriers were provided, and concluding reflections and recommendations were presented.